Analisis profitabilitas dalam isu perubahan iklim global pada CV. Kelapa Inti Murni - Bunga, Vanesa Putri; Maradesa, Djeini (Yayasan Widyantara Nawasena Raharja, 2024)
Climate change is a global issue that remains a significant topic of discussion among many countries, including Indonesia. This is clearly expected to impact companies in areas such as sales and company profits. To analyze the risks and opportunities related to climate change on the profits generated by a company, it is essential to measure using profitability ratios. Profitability measures a company’s ability to generate profit from a certain level of sales, assets, and equity capital. This study aims to analyze the profitability in the context of global climate change issues at CV. Kelapa Inti Murni. This research is qualitative with a descriptive approach. The types of data used are quantitative and qualitative. Data sources include primary and secondary data. Data collection methods used are observation, interviews, and document analysis. The data analysis method employs profitability ratios. The research findings indicate that profitability at CV. Kelapa Inti Murni is related to climate change. If there is a climate change event such as excessive heat, the company's profitability is expescted to decrease due to reduced sales or minimal profits. Overall, the company's profitability is considered quite good as it is above the industry average, except for return on equity which remains below the industry average standard.